Clinical factors associated with hemoglobin recovery after ferric carboxymaltose administration in patients with non-malignant gastrointestinal bleeding–related iron-deficiency anemia - Sayaka Tsuji; Kazuhiro Ota; Shun Sasaki; Akitoshi Hakoda; Noriaki Sugawara; Taro Iwatsubo; Kosuke Tsuda; Kazuki Kakimoto; Hideaki Morita; Hiroki Nishikawa (BMC Gastroenterology, 2026)
Abstract Objective Ferric carboxymaltose (FCM) enables rapid iron repletion in gastrointestinal bleeding–related iron-deficiency anemia (IDA), but clinical factors associated with hemoglobin (Hb) recovery in real-world practice remain unclear. We aimed to identify clinical factors associated with achieving robust Hb recovery after FCM administration. Methods This retrospective cohort study included adults aged ≥ 18 years who received FCM for suspected gastrointestinal bleeding–related IDA. Patients with baseline Hb ≥ 10.0 g/dL, malignant tumors, gynecologic bleeding, or anemia attributable to non-gastrointestinal causes were excluded. Robust Hb recovery was defined as an Hb increase ≥ 2.0 g/dL within 12 weeks without transfusion. Baseline characteristics were compared according to whether this criterion was met, followed by multivariable logistic regression. A sensitivity analysis excluding transfused patients was conducted. Results Of 601 patients who received FCM, 170 were eligible, and 94 (55.3%) met the robust Hb recovery criterion. These patients were younger and had lower mean corpuscular volume, C-reactive protein, serum ferritin, and serum iron levels. Younger age (adjusted odds ratio [aOR], 0.96; 95% confidence interval [CI], 0.94–0.98) and anticoagulant use (aOR, 2.61; 95% CI, 1.16–5.90) were independently associated with meeting the criterion. Sensitivity analysis yielded consistent results. Conclusion Younger age and anticoagulant use were associated with study-defined robust Hb recovery after FCM administration in patients with gastrointestinal bleeding–related IDA; however, the association with anticoagulant use was exploratory. Suboptimal Hb recovery may reflect ongoing blood loss or competing causes of anemia rather than reduced biological responsiveness to intravenous iron and should prompt clinical reassessment.